Pendekatan Scientifik Approach Dalam Pembelajaran Pendidikan Agama Islam (PAI) - Defi Fefdianti (FATAWA: Jurnal Pendidikan Agama Islam, 2022)
Islamic religious education is a conscious effort to foster and nurture students so that they can always understand the teachings of Islam as a whole (kaffah) and then live the goals that ultimately practice and make Islam a way of life. The application of a scientific approach in learning does not only focus on how to develop student competence in conducting observations or experiments, but how to develop knowledge and thinking skills so that they can support creative activities in innovating or working. The criteria for scientific learning are as follows: (1) learning based on facts or phenomena that can be explained by logic, (2) teacher explanations, student responses, and student teacher educative interactions are free from reasoning that deviates from the flow of logical thinking. (3) Encourage and inspire students to think critically. (4) Encouraging and inspiring students to be able to think hypothetically, (5) Encouraging and inspiring students to be able to understand, apply, and develop rational and objective thinking patterns, (6) Based on concepts, theories, and empirical facts that can be accounted for. (7). Learning objectives are formulated in a simple, clear, and attractive presentation system. While the learning process must avoid non-scientific traits or values ​​including: intuition, common sense, prejudice, discovery through trial and error, and from critical thinking. The steps in scientific learning include: (1) Observing (observing), (2) Questioning (asking), (3) Experimenting (trying), (4) Associating (reasoning), (5) Networking (forming a network).